AKSESIBILITAS ANAK DAN KONSTRUKSI DIRI PADA FACEBOOK - Adeni, Susri (Komuniti: Jurnal Komunikasi dan Teknologi Informasi, 2014)
Facebook is not only used by teens or adult, but also children of primary school age, ranging from grade 4 (four) to grade 6 (six) or starting from the age of 8-12 years. This is an interesting fact because basically a requirement to have an account on Facebook is aged 17 years and over. So these children manipulate their data in order to have Facebook. The purpose of this study is to determine the children?s access to the facebook identify their activities in using Facebook, describe the shiftof social interaction (direct interaction or face to face ) into digital interaction and to assess the use ?of facebook as a forum for self-construction. Type of research is qualitative research. This research is conducted in the Elementary School (SDN) in the city of Bengkulu with purposive method where a public elementary school located in the suburbs or border; then it is set that SDN 71 Bengkulu City. Results show that children of school age have made use of facebook as a tool to communicate with other friends from various means at their disposal . In terms of social interaction and digitalinteractions, it can not be said that the child has fully entered the digital interaction.